A local spatial analysis criterion of post-traumatic brain injury and accessibility to public transportation - Vaz, Eric; Foster, Akeem; Cusimano, Michael (Journal of Tourism, Sustainability and Well-being, 2017)
Reported cases of traumatic brain injuries are increasing among the Canadian population. With an annual rate of 187,000 reported cases a year and growing, there is an extrapolated growth of 239,000 cases of traumatic brain injuries occurring annually by 2036. As Ontario intends to be a completely accessible province for those with disabilities by 2025, this paper utilizes GIS to visualize and better understand the relationship between post-TBI residents living in Brampton and their accessibility to public transportation. As Brampton is currently the most expensive city to insure a vehicle because of frequent collisions occurring within the city, creating a more accessible, reliable, and efficient public transportation system can integrate those who have experienced a traumatic brain injury back into society while reducing the required use of a personal vehicle. This will contribute to a safer city, as there are fewer vehicles on the road at risk of being involved in a road accident. There are also further benefits to this, as it will also reduce levels of congestion in the foreseeable future.